A Proton Conductive Porous Framework of an 18‐Crown‐6‐Ether Derivative Networked by Rigid Hydrogen Bonding Modules - Chen, Xin; Huang, Rui‐Kang; Takahashi, Kiyonori; Noro, Shin‐ichiro; Nakamura, Takayoshi; Hisaki, Ichiro (Angewandte Chemie International Edition, 2022)
A rigid hydrogen‐bonded organic framework (HOF) was constructed from a C3‐symmetric hexatopic carboxylic acid with a hydrophilic 18‐crown‐6‐ether (18C6) component. Despite the flexible macrocyclic structure with many conformations, the derivative with three 4,4’‐dicarboxy‐o‐terphenyl moieties in the periphery yielded a rigid layered porous framework through directional intermolecular hydrogen bonding. Interestingly, the HOF possesses 1D channels with bottleneck composed of 18C6 rings. The HOF shows proton conductivity (1.12×10−7 S cm−1) through Grotthuss mechanism (Ea=0.27 eV) under 98 %RH. The present unique water channel structure provides an inspiration to create molecular porous materials. A porous hydrogen‐bonded framework (HOF) was constructed from a 18‐crown‐6‐ether (18C6) derivative. Although a 18C6 macrocycle is flexible and has many possible conformations, directional intermolecular hydrogen bonds of 4,4′‐dicarboxy‐o‐terphenyl modules in the periphery of the 18C6 allowed to form a rigid HOF with 1D channels with a bottleneck composed of 18C6 rings. The wet HOF shows proton conductivity (1.12×10−7 S cm−1) through a Grotthuss mechanism (Ea=0.27 eV) under 98 %RH.